Evaluasi Teknik Pembelajaran Berbasis Proyek (Project-Based Learning) yang Diterapkan oleh Dosen: Studi Literatur - Marwah Marwah; Dedy Ari Nugroho; Syarifuddin, Syarifuddin (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This study evaluates the effectiveness of Project-Based Learning (PBL) techniques applied by lecturers in higher education based on a literature study. The research method in this study uses the literature method. The study results show that PBL is able to improve the quality of learning by encouraging active student participation, as well as strengthening problem-solving, collaboration, and communication skills. However, the implementation of PBL also faces several challenges, including the need for lecturer training, greater time allocation, and adequate institutional support. Evaluation in PBL requires diverse and comprehensive assessment methods to measure student learning outcomes fairly and accurately. With good preparation and adequate support, PBL can be an effective and beneficial learning method in higher education.